Vervet monkeys socialize more when time budget constraints are experimentally reduced - Borgeaud, C; Jankowiak, B; Aellen, M; Dunbar, RIM; Bshary, R (Wiley, 2021)
In species that live in stable groups, successful management of time budget (i.e., the proportion of time involved in different behaviours) and social relationships has been proposed to be a key variable affecting individual fitness. Such management is limited by time constraints, which are group size and season dependancy. However, the link between time budget constraints and grooming patterns as a means to service social relationships has never been studied experimentally. Here, we reduced the time constraints of three wild vervet monkey (Chlorocebus aethiops pygerythrus) groups by offering them high quality food for 60 min in the morning. We conducted 10 trials in summer and 10 trials in winter. We found that vervet monkeys indeed reduced the proportion of time spent foraging during the rest of those days compared to control days and increased the proportion of grooming time spread over more bouts. Individuals that did not get access to the food still participated as much in grooming as those that did eat. In accordance with our expectations, social network analysis revealed a larger grooming network on supplementation days: vervet monkeys used their extra time to socialize with more different group members. Furthermore, following our predictions, the effect of provisioning was usually stronger during the winter season (when food was scarce and days shorter) than during the summer, and the number of conflicts decreased during supplementation days. Finally, despite the fact that adults and juveniles of all three groups increased their proportion of time spent grooming during supplementation days, few group and age differences emerged in the way vervet monkeys manage their time budget. Interestingly, some of these differences seem to be independent of group size. In conclusion, vervet monkeys seize the opportunity to increase the proportion of time spent in social behaviours if time budget constraints are reduced.